Предмет: Алгебра,
автор: shipunovaln
доказать, что
(x-y)²-2x(x-y)=y²-x²
Ответы
Автор ответа:
3
(х-у)^2-2х(х-у)=у^2-х^2
(х-у)^2 расписывается как х^2-2ху+у^2
-2х(х-у)=-2х^2+2ху
х^2-2ху+у^2-2х^2+2ху=у^2-х^2
-х^2+у^2=у^2-х^2, или
у^2-х^2=у^2-х^2
Доказано.
(х-у)^2 расписывается как х^2-2ху+у^2
-2х(х-у)=-2х^2+2ху
х^2-2ху+у^2-2х^2+2ху=у^2-х^2
-х^2+у^2=у^2-х^2, или
у^2-х^2=у^2-х^2
Доказано.
Похожие вопросы
Предмет: Математика,
автор: littleLucy
Предмет: Математика,
автор: kristinarassoha75
Предмет: Химия,
автор: dashamik067
Предмет: Математика,
автор: SHRD